Baba Is You: Doing Things With Words - Silva Campos, Simone (Loading)

(untitled) (Canadian Game Studies Association, 2021)
Baba Is You is a 2D electronic game in which the player-controlled character pushes word-blocks around in order to build sentences, which make up the rules governing the simulated environment. With Baba Is You as the case in point, we bring up parallels between video games and Wolfgang Iser’s reader-response theory, J.L. Austin’s pragmatics, and Gregory Bateson’s levels of learning. By considering self-reference paradoxes, metalanguage, and the map-territory distinction, Baba Is You becomes an intuitive philosophic playground by enticing players to question not only language and its uses, but some general conceptions about not just video games, but life itself.